Cooperation of RNA-Binding Proteins – a Focus on Roquin Function in T Cells - Behrens, Gesine; Heissmeyer, Vigo (Frontiers in Immunology, 2022)
Post-transcriptional gene regulation by RNA-binding proteins (RBPs) is important in the prevention of inflammatory and autoimmune diseases. With respect to T cell activation and differentiation, the RBPs Roquin-1/2 and Regnase-1 play pivotal roles by inducing degradation and/or translational silencing of target mRNAs. These targets encode important proinflammatory mediators and thus Roquin and Regnase-1 functions dampen cellular programs that can lead to inflammation and autoimmune disease. Recent findings demonstrate direct physical interaction of both RBPs. Here, we propose that cooperativity of trans-acting factors may be more generally used to reinforce the regulatory impact on selected targets and promote specific cell fate decisions. We develop this concept for Roquin and Regnase-1 function in resting and activated T cells and discuss the involvement in autoimmunity as well as how the therapeutic potential can be used in anti-tumor therapies.